(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The realm of wrestling, especially for young athletes, demands a harmonious blend of physical fitness, tactical skill, mental strength, and character development. This article elucidates the critical importance of training young wrestlers, emphasizing the multifaceted nature of the sport. Through a detailed methodological approach, we present a comprehensive training regimen that encompasses strength building, skill drills, agility enhancement, mental conditioning, and recovery strategies. The goal is to not only sculpt young wrestlers into formidable athletes but also instill values of discipline, respect, and perseverance. The conclusion underscores the dual reward of such training: achieving excellence in the sport while simultaneously cultivating life skills that transcend the wrestling mat.